2014
DOI: 10.2217/pgs.14.153
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and Risk of Major Bleeding During Warfarin Treatment

Abstract: Aim To determine whether genetic variants associated with warfarin dose variability were associated with increased risk of major bleeding during warfarin therapy. Materials & methods Using Vanderbilt’s DNA biobank we compared the prevalence of CYP2C9, VKORC1 and CYP4F2 variants in 250 cases with major bleeding and 259 controls during warfarin therapy. Results CYP2C9*3 was the only allele that differed significantly among cases (14.2%) and controls (7.8%; p = 0.022). In the 214 (85.6%) cases with a major bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 42 publications
3
42
0
Order By: Relevance
“…This association was not significant in African-Americans, likely due to a lack of statistical power (only 1 TT homozygous subject). The finding of decreased INR variability associated with the T allele of this CYP4F2 variant is concordant with findings in recent studies of genetic risk factors for major bleeding in patients receiving warfarin that suggested a lower risk of bleeding in subjects bearing the minor T allele [13, 15]. …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This association was not significant in African-Americans, likely due to a lack of statistical power (only 1 TT homozygous subject). The finding of decreased INR variability associated with the T allele of this CYP4F2 variant is concordant with findings in recent studies of genetic risk factors for major bleeding in patients receiving warfarin that suggested a lower risk of bleeding in subjects bearing the minor T allele [13, 15]. …”
Section: Discussionsupporting
confidence: 89%
“…For example, the risk of bleeding or thrombosis was increased long after the initial 2 week dose-titration phase in patients with genotypes associated with altered warfarin sensitivity [12, 13]. The mechanisms whereby genotype might affect complications of warfarin therapy beyond the dose-titration phase are not known.…”
Section: Introductionmentioning
confidence: 99%
“…Although older people are more likely to bleed [36], the bleeding events are likely to be mainly due to the incorrect warfarin dose since there is a high percentage of subjects with supratherapeutic INR (i.e., 88%). The higher number of CYP2C9*3 alleles in uncontrolled patients is in line with recent studies that indicated an increased bleeding risk of CYP2C9*3 carriers [37,38]. However, CYP2C9 alleles (*2 and *3) are not associated with the therapeutic warfarin doses future science group Research Article Karaca, Bozkurt, Cesuroglu et al in our controlled patients.…”
Section: Discussionsupporting
confidence: 87%
“…Tomek et al [38] showed that anticoagulated Caucasian patients carriers of 3 variant alleles of the genes CYP2C9 and VKORC1 exhibited a significantly higher risk of major bleeding during the initiation and maintenance phases of warfarin therapy. Kawai et al [39] showed that the CYP2C9∗3 allele could double the risk of major bleeding among patients administered warfarin for 30 or more days. However, the authors did not find any association with VKORC1 variants and the study population largely consisted of Caucasians, although it also included Afro-Americans and others ethnic groups.…”
Section: Discussionmentioning
confidence: 99%